Help! -Negate statement then reexpress as equiv positive statement

1. The problem statement, all variables and given/known data
$\forall$a $\in$A$\exists$b$\in$B(a$\in$C $\leftrightarrow$ b$\in$C).

2. Relevant equations

3. The attempt at a solution\forall

This is equivalent to $\exists$a$\in$A$\neg\exists$b$\in$B(a$\in$C $\leftrightarrow$b$\in$C).
1. The problem statement, all variables and given/known data
1. The problem statement, all variables and given/known data

2. Relevant equations

3. The attempt at a solution

 PhysOrg.com science news on PhysOrg.com >> Heat-related deaths in Manhattan projected to rise>> Dire outlook despite global warming 'pause': study>> Sea level influenced tropical climate during the last ice age
 The first part of your solution appears correct however you still need to negate that which is in the parantheses. It may help to write out the logical operators in words to give you a better picture of the question. I came up with a solution, but I will wait to post till you give the rest of your problem a shot.